2019
DOI: 10.1111/liv.14246
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of canonical Wnt/β‐catenin signalling in hepatic dendritic cells triggers autoimmune hepatitis

Abstract: Background & AimsAutoimmune hepatitis (AIH) is a chronic inflammatory liver disease manifested with the aberrant activation of hepatic dendritic cells (HDCs) and the subsequent breakdown of immune homeostasis. As an important player, HDC maintains immunological balance between tolerance to self‐antigens versus destruction against pathogens in liver. However, the intracellular signalling networks that program HDC remain unclear. We have now found the role of canonical Wnt/β‐catenin signalling in HDCs.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Therefore, an increase in this molecule might lead to the overreaction of cDCs, which results in systematic immune imbalance. Quantitative and functionality alterations of human DC cells have been reported in many autoimmune diseases [25][26][27][28][29] , yet the role of cDC in AIH has been elusive. Using the fresh peripheral blood and liver section of AIH patients and healthy controls, we demonstrated that mature cDCs played a detrimental role in promoting AIH, and then, a mouse EAH model was used to validate the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an increase in this molecule might lead to the overreaction of cDCs, which results in systematic immune imbalance. Quantitative and functionality alterations of human DC cells have been reported in many autoimmune diseases [25][26][27][28][29] , yet the role of cDC in AIH has been elusive. Using the fresh peripheral blood and liver section of AIH patients and healthy controls, we demonstrated that mature cDCs played a detrimental role in promoting AIH, and then, a mouse EAH model was used to validate the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagy process is often used to eliminate damaged or unwanted organelles and remove intracellular microbial pathogens, which play a significant role in the pathogenesis of liver disease 32,33 . Role of autophagy in dendritic cells have been reported to be associated with the following mechanisms: (i) autophagic pathways could promote MHC-II antigenpresentation, that is, autophagy could be used to direct pathogens into autophagosomes and then the fusion with lysosomes, 28,[34][35][36] (ii) autophagy could down-regulate antigen presentation on MHC-I molecules during anti-viral CD8 + T cell responses, 37,38 (iii) autophagy could accelerate cytokine production 39,40 . Most studies have found that autophagy enhancement was associated with BMDC maturation and antigen presentation after activation of Toll-like receptor (TLR) signaling pathways [41][42][43] , while other studies identified that new drug therapies could decrease DC maturation and function by enhanced autophagy 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Application of Wnt signaling agonists increased the activity of SOD and GSH-PX and improved behavioral deficits in rats with Parkinson's disease [ 40 ]. The deficiency of this pathway gives rise to T cell-mediated immune response and incidence of AIH [ 41 ]. The Wnt/ β -catenin plays an anti-inflammatory effect on pigs during bacterial infection [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic dendritic cell (HDC), as a unique organ-resident DCs subtype, was the major contributor to sustain tolerance conditions in liver 56 .One latest study reported that the deficiency of Wnt signaling pathway in HDCs was found in both AIH patients and the Con A- induced AIH mouse model, and reinvigorating this signaling with a Wnt agonist successfully alleviated the progression of AIH. It is indicated that Wnt signaling pathway in HDCs exerts vital functions on maintenance of the liver homeostasis and their loss altered the immune environment to T cell activation 57 . The Hippo signaling pathway, which is evolutionarily conserved, has multiple biological functions in homeostasis and regeneration of tissues or organs.…”
Section: Discussionmentioning
confidence: 99%